2D‐TMDs based electrode material for supercapacitor applications. (2nd October 2022) - Ali, Muhammad; Afzal, Amir Muhammad; Iqbal, Muhammad Waqas; Mumtaz, Sohail; Imran, Muhammad; Ashraf, Faria; Ur Rehman, Asad; Muhammad, Faqeer
Summary: Transition metal dichalcogenides (TMDs) have been attracted the researchers to design high‐performance electrodes to elevate power and energy density for better performance of energy storage devices. The attraction is due to the better surface area, high conductivity with distinct oxidation states, and the layered structure of TMDs. These characteristics persuade the TMDs to be the most favorable contenders to store energy via a cross‐charge storage structure. TMDs belong to the family of two dimensions (2D) materials. This review article focused on graphene, molybdenum disulfide (MoS2 ), and tungsten disulfide (WS2 ) based electrode materials for supercapacitor applications. MoS2 showed remarkable chemical/physical characteristics like tunable bandgap, specific surface area, mechanical friction, and high wear resistance. The researchers showed that the nanostructured materials of MoS2 have exceptional characteristics and tremendous potential as supercapacitor electrodes. The MoS2 composites have porous and hollow structures that display better energy storage characteristics. MoS2 has excellent potential to fill the gap as an electrode material for energy storage devices and eco‐friendly applications. There is much opportunity for scientific progress in the interdisciplinary sector. The nanostructures of WS2 have auspicious qualities like good surface area, and excellent electrochemical characteristics, which make the WS2 a super candidate for supercapacitor application. The WS2 ‐based composites also showed excellent results for supercapacitors and other energy storage devices. Herein we study comparatively the properties of these materials discus as capacitance, energy density, power density, rate of retention, cyclic stability, and electrochemical properties.